2021
DOI: 10.1177/09544062211053181
|View full text |Cite
|
Sign up to set email alerts
|

Free and forced vibration analysis of flyash/graphene filled laminated composite plates using higher order shear deformation theory

Abstract: The strength of the conventional composite plates can be enhanced by the use of additional fillers. These composite plates are often subjected to dynamic loading conditions which necessitate the study of their static and dynamic behavior. In this study, laminated composite plates (LCP) are fabricated by open layup process with epoxy as a base resin, E-glass fiber as reinforcement, and fillers: flyash and graphene. The fillers are included in order to improve the mechanical properties of the composite. The fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The experimental results showed that the damage deviation of this method was less than 4.5 %. Parida and Jena [22] reinforced polymer composites with manual layering technology, and calculated LCP under simple harmonic load based on finite element analysis. The results showed that the addition of graphene can enhance the buckling strength of LCPs.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the damage deviation of this method was less than 4.5 %. Parida and Jena [22] reinforced polymer composites with manual layering technology, and calculated LCP under simple harmonic load based on finite element analysis. The results showed that the addition of graphene can enhance the buckling strength of LCPs.…”
Section: Related Workmentioning
confidence: 99%
“…The order of the displacement fields set the accuracy of the results. According to Parida and Jena’s modified fifth-order shear deformation theory ( Parida and Jena, 2021b; 2022 ) , the displacement fields (u, v, and w) in the x, y, and z directions are given by where u 0 , v 0 , and w 0 are the static mid-plane deflection of LCP in x, y, and z directions.…”
Section: Constitutive Relation and Nonlocal Theorymentioning
confidence: 99%
“…The strength-toweight ratio of conventional composites can be improved by adding fillers along with the other constituents [1]. The static and dynamic performance of the composite plates enriched with added filler is enhanced [2][3][4]. Although there is an increase in the mechanical strength of the composites with the addition of filler materials, continuous exposure of these materials to dynamic environments in industrial or household applications causes gradual degradation of the strength of the composite components or beam structures.…”
Section: Introductionmentioning
confidence: 99%